Covidiots and the Clamour of the Virus-as-Question: Some Reflections on Biomedical Culture, Futurity and Finitude. Issue 2 (1st June 2020) - Lim, Bryan
Abstract: Drawing on my experience with gay men in London who, despite COVID-19-related public health guidelines, continue to meet up and congregate so as to engage in a myriad of sexual (and non-sexual) practices, this article grapples with how an insistence on pre-pandemic intimacies of bodily interactions during a pandemic might prompt us to reconsider our relationship with biomedicine. While these covidiots' experiments with mortality in the form of dance parties, orgies and casual hook-ups may not be ethically exemplary, this article argues that they are at the very least ethically interesting because they serve as lures through which our other intimacies with temporality, futurity and finitude may be reconsidered.